Implementation of Differentiation in the Discovery Learning Model to Improve Student Learning Outcomes on Newton’s Law Topics - Neli Darnia; Haratua Tiur Maria; Erwina Oktavianty (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to determine the improvement in students' learning outcomes on Newton's Laws material at SMA Kemala Bhayangkari 1 Kubu Raya, through differentiated learning using the discovery learning model. The research design employed is a quasi-experimental design with a nonequivalent control group design. The research sample consisted of Class XI Physics 1 and Class XI Physics 2, each with 31 students, selected using the intact group random sampling technique. The instrument used was a test. The data were analyzed using descriptive and inferential statistical analysis techniques. In the pretest, the experimental class obtained a score of 25.16, and the control class 15.48, both falling  in the low category. After the treatment, the experimental class's posttest score increased to 84.83 (high category), while the control class reached 50 (medium category). Based on Cohen’s d effect size value, the effectiveness of implementing differentiated learning with the discovery learning model in improving learning outcomes was 2.042, which falls into the high category. In addition, based on a learning style questionnaire, 20 students preferred the auditory learning style. This study concludes that the implementation of differentiated learning using the discovery learning model is effective in improving students' learning outcomes on Newton’s Laws material.